Chile : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Chile. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
The Chilean economy is recovering from a prolonged slowdown that started with the decline in copper prices in 2011 and intensified over the past two years. The new administration, which took office in March, aims at reinvigorating investment and economic growth through structural reforms, but a divided Congress may constrain the reform space.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet